2021
DOI: 10.1021/acsmacrolett.1c00519
|View full text |Cite
|
Sign up to set email alerts
|

Commodity Polymers to Functional Aminated Materials: Single-Step and Atom-Economic Synthesis by Hydroaminoalkylation

Abstract: Hydroaminoalkylation (HAA) is demonstrated to be a promising postpolymerization route to catalytically prepare amine-functionalized atactic polypropylene. Using a recently reported tantalum catalyst supported by a N,O-chelating cyclic ureate ligand, vinyl-terminated polypropylene (VTPP) is transformed into both aryl and alkyl secondary amine-terminated polyolefins. Early transition-metal-catalyzed hydroaminoalkylation avoids protection/deprotection protocols typically required for secondary amine synthesis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…91 Our work on tantalum-catalyzed hydroaminoalkylation of vinyl terminated polypropylene (VTPP) demonstrated that hydroaminoalkylation is a viable postpolymerisation amination method and regioselective formation of the branched products was observed. 61 Such postpolymerization modifications can be challenging to catalyze due to the limited solubility and viscosity of the polymer, but the reactivity of the Ti(NMe 2 ) 4 / L1 system with challenging and diverse alkene substrates 31 ( vide supra ) suggests that this system could also be used with challenging macromolecular substrates for postpolymerisation (Table 1) and would offer a “green” advance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…91 Our work on tantalum-catalyzed hydroaminoalkylation of vinyl terminated polypropylene (VTPP) demonstrated that hydroaminoalkylation is a viable postpolymerisation amination method and regioselective formation of the branched products was observed. 61 Such postpolymerization modifications can be challenging to catalyze due to the limited solubility and viscosity of the polymer, but the reactivity of the Ti(NMe 2 ) 4 / L1 system with challenging and diverse alkene substrates 31 ( vide supra ) suggests that this system could also be used with challenging macromolecular substrates for postpolymerisation (Table 1) and would offer a “green” advance.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is also observed with the tantalum catalyzed hydroaminoalkylation which required 20 mol% tantalum catalyst for VTPPs with M n = 8500 g mol −1 . 61…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high reactivity observed with the cyclic ureate catalyst has made this system suitable for postpolymerization modification for functional materials synthesis (Scheme 27). 110 Using Ta-catalyzed hydroaminoalkylation, vinyl-terminated polypropylene can be directly and quantitatively converted to amine-terminated polypropylene. Early transi- tion-metal, atom-economic hydroaminoalkylation is ideally suited for postpolymerization modification, as there are no byproducts and no deprotection protocols required.…”
Section: Early Transition-metalmentioning
confidence: 99%